Barriers to Social Service Access for Ukrainian Refugees with Disabilities in Georgia: Outreach and Communication - Kateryna Ihnatenko; Shorena Sadzaglishvili (Social Sciences)
This paper aims to identify the barriers to accessing social services for persons with disabilities among Ukrainian refugees and to examine how stakeholders can reach them through communication channels. The article analyzes the challenges faced by disabled Ukrainian refugees in Georgia. We employed a mixed methods approach to address this objective, combining quantitative and qualitative research methods. We surveyed 114 Ukrainian refugees with disabilities, aged 18 to 60+ (n = 114), residing in Georgia, and conducted semi-structured interviews with 26 experts from civil society organizations assisting Ukrainian refugees, as well as 6 caregivers with diverse roles (e.g., mother, daughter, husband). The findings reveal significant difficulties faced by Ukrainian refugees with disabilities in accessing essential services such as healthcare, employment, psychological counseling, rehabilitation, early intervention services, legal aid, and information. The primary strategies employed by stakeholders providing humanitarian aid include individualized approaches and communication. However, while many nongovernmental organizations (NGOs) assist Ukrainian refugees, there are currently no NGOs specifically focused on supporting children and adults with disabilities in this population.